2018
DOI: 10.22271/tpr.2018.v5.i2.027
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation potential of Indian mustard (Brassica juncea var. arawali) and fenugreek (Trigonella foenum-graecum L.) planted on lead and nickel contaminated soil

Abstract: The aim of the present study was to examine the accumulation potential of Indian mustard (Brassica juncea var. arawali) and fenugreek (Trigonella foenum-graecum) plants in lead and nickel contaminated soil. Plants were exposed to higher concentrations of Pb and Ni (800 mg l -1 ). EDTA and SA were amended at 2.4 mM concentrations. Plants were harvested and ovendried. The accumulation of Pb and Ni in plants was determined and their effects on plant growth were evaluated for both species. Seed germination rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Burning of hyper‐metal accumulator plants further contributes to emission of toxic metals in atmosphere. [ 66 ]…”
Section: Resultsmentioning
confidence: 99%
“…Burning of hyper‐metal accumulator plants further contributes to emission of toxic metals in atmosphere. [ 66 ]…”
Section: Resultsmentioning
confidence: 99%
“…And there was a gradually decrease in the lead BAF values at Pb levels has been applied, but overall, all treatments showed high BAF values indicating that these plants accumulate Pb in their roots and then translocated it from roots to the aerial (Suman et al, 2018). The obtained values of Pb BAF ˃1 demonstrated that mustard and corn considered as a Pb accumulators (Aladesanmi et al, 2019) (Kaur, 2018). In addition, the values of lead (TF) for mustard and mays were shown in figure (6).…”
Section: The Bioaccumulation Factor Of Leadmentioning
confidence: 97%
“…The pollutants are degraded either through accumulation, filtration or dissipation. In the current scenario, the need of the hour is realizing the consequences of heavy metal pollutants in soil and water (Kaur, 2018). Heavy metal pollutants, the half-life is much more than that of organic pollutants like pesticides and petroleum by-products.…”
Section: Introductionmentioning
confidence: 99%